Formulation and Development of an Experimental Polishing Paste with Antimicrobial Activity Based on Coturnix coturnix (Codorniz) Eggshell - Frank Mayta-Tovalino; Alicia Fernández-Giusti; Joyce Del Pino; Daniel Alvitez-Temoche; Roman Mendoza; Abigail Temoche; Arnaldo Munive-Degregori (International Journal of Dentistry)
Aim. To formulate and develop a new experimental polishing paste based on Coturnix coturnix eggshell and to evaluate its abrasive, remineralizing, and antibacterial activities. Materials and Methods. The research was experimental, longitudinal, comparative, and prospective. To measure the antibacterial efficacy, analysis units consisted of wells were made. The microorganisms S. aureus, E. coli, E. faecalis, C. albicans, and S. mutans were inoculated with experimental paste (Coturnix coturnix quail eggshell base) and control paste (Universal Polishing and Diamond Excel) consisting of n = 12 for each group. Results. It was found that, among the strains inoculated, the quail paste presented with the highest antimicrobial effectiveness to C. albicans and S. mutans with an average of 8.70 ± 0.14 and 11.65 ± 0.15 mm, respectively. On the other hand, the Universal Polishing paste only had an average of 7.00 ± 0.11 and 8.71 ± 0.11 mm for C. albicans and S. mutans, respectively. Significant differences were observed only in these two strains p<0.001. Conclusions. The quail paste demonstrated antimicrobial efficacy against C. albicans and S. mutans compared to control paste, Diamond Excel, and Universal Polishing according to the time and type of microorganism.